Aspek Kepribadian Tokoh Utama Dalam Drama Ayahku Pulang Karya Usmar Ismail Dan Implementasinya Dalam Pembelajaran Sastra Di SMP (Kajian Psikologi Sastra) - Haryanti, Nofita Endah; , Prof. Dr. Ali Imron Al-Ma'rufM.Hum (2016)
The purpose of this study was to describe: (1) describe the elements that build drama Round My father works Usmar smail; (2) describe aspects of the personality of the main character in the drama My father works Round Usmar Ismail learning in junior high literature study Psychology iterature; (3) describes the implementation aspects of the personality of the main character in the drama My dad Round Usmar Ismail works in literature learning in SMP (Psychology Literature). This study used descriptive qualitative method. The data source of this research is the work of playwright father Round Usmar Ismail. The data in this study a word, phrase, clause sentences and paragraphs in work Round father plays Usmar Ismail. This research data collection techniques using the technique of reviewing documents and archives (content analysis). Technical analysis of the data using the model of semiotic reading method includes reading heuristics and hermeunetik. The findings of this study indicate that: (1) Scene Round father in the drama that is regret a child who has squandered his father, who for so long has left his family. Flow used in Round My father drama that highlight the flow-through (flash back). My father is a character in the drama Gunarto, Tina (Mrs.), Raden Saleh (Father), Mintarsih, Maimun. Background happening place generally in a modest house and outside the house near the bridge. Background time in Round My father drama happened at dusk during the month of Ramadan when heavy rain. Social background in drama Round My father took a social setting way of thinking and backward, the main character always berfikiran negativ against his own father. The conversation in the drama My father using a dialog style Round ping pong; (2) Aspects of the main characters in the drama personality Round father selfish private, personal stubborn, personally hateful, vindictive person and personal dignity; (3) Implementation aspects of the main characters in the drama of personality Round My father works Usmar Ismail learning in junior high literature study psychology literature, especially in class VIII is at SK 5, appreciate the drama performances, and KD 5.2 evaluating character actor in a drama performance. Keywords: personality aspects, drama Ayahku Pulang, learning psychology, learning in junior hight school literature